PEMANFAATAN DIGITAL CANVASSING DALAM RANGKA OPTIMALISASI PENJUALAN PADA BAKPIA WONG - Susanto, Denies; Ridwan, Ade (Gapenas Publisher, 2025)
Improving competitiveness and marketing effectiveness is a challenge faced by many entrepreneurs, including traditional culinary industries such as Bakpia Wong. Despite having quality products with a distinctive taste, this small and medium-sized enterprise (SME) often faces limitations in marketing and efficiently disseminating product information. One marketing method that can be optimized is the use of digital canvassing, a digital marketing strategy aimed at reaching a wider audience with more cost-effective means. The main issue faced by Bakpia Wong is the lack of utilization of digital technology to increase market reach and customer interaction. This results in untapped market potential. Additionally, the reliance on conventional marketing methods limits the business's competitiveness in an increasingly digital world. The proposed solution is the implementation of digital canvassing through digital platforms such as social media, messaging apps, and e-commerce websites to facilitate promotions and transactions. By using digital canvassing, Bakpia Wong can enhance the visibility of its products among potential customers, as well as simplify the ordering and delivery process. This strategy will include creating engaging promotional content, managing social media accounts professionally, and utilizing digital tools to gather direct customer feedback to improve product quality and services. The proposed activities include several phases. First, training for the owners and staff of Bakpia Wong on the use of digital platforms and digital marketing techniques. Second, the development and design of digital content that aligns with the target market's characteristics, including the use of attractive product photos and videos and effective social media management. Third, monitoring and evaluating the effectiveness of the applied digital canvassing strategy by measuring increases in customer interaction, sales, and customer satisfaction. The expected outcomes of this initiative include an increase in Bakpia Wong's sales volume, enhanced brand recognition, and the formation of better relationships with customers through digital platforms. Additionally, it is hoped that the business owners will be able to continuously leverage digital technology for future business growth. The utilization of digital canvassing is expected to have a positive impact not only on Bakpia Wong but also on the development of other potential culinary SMEs in the digital era.